Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 32-6.(8-23)+18
= 32 - 6 . (8 - 8) +18
=32 - 0 +18
= 50
b) (3.5-9)3.(1+2.3)2+42
= (15-9 )3. (1+6)2 + 4 2
= 63 . 7 2 + 42
= 216 x 49 + 16
= 10584 + 16
=10600
c) 9234:[3.3.(1+83)]
= 9234 : [ 3.3.93]
= 9234 : [ 3.3 . 729]
= 9234 :6561
= 1,407407407
d) 76- {2.[2.52-(31-2.3)]}+3.25
= 76 - { 2. [ 2.52 - ( 31 - 6)]} + 3.25
= 76 - { 2 . [ 2. 52 - 25 ]} + 3 .25
= 76 - { 2 . [2. 25 - 25]} + 3.25
= 76 - { 2.[ 50 - 25 ]} + 3.25
= 76 - { 2. 25} + 3 . 25
= 76 - 50 + 3. 25
= 76 - 50 + 75
= 101
=> 5^2x-3 = 5^2.3 + 5^2.2 = 5^2.(2+3) = 5^2.5 = 5^3
=> 2x-3 = 3
=> 2x = 3+3 = 6
=> x = 6:2 = 3
Vậy x = 3
Tk mk nha
a: \(\Leftrightarrow\left[\left(3x+14\right):4-3\right]:2=1\)
=>(3x+14):4-3=2
=>(3x+14):4=5
=>3x+14=20
=>3x=6
hay x=2
b: \(\Leftrightarrow\left[\left(x:4+17\right):10+3\cdot16\right]:10=5\)
\(\Leftrightarrow\left(x:4+17\right):10=50-48=2\)
=>x:4+17=20
=>x:4=3
hay x=12
c: \(\Leftrightarrow2\cdot15^2+\left[2\cdot125-\left(2x+4\right)\cdot5\right]:19=453\)
\(\Leftrightarrow250-\left(2x+4\right)\cdot5=\left(453-450\right)\cdot19=57\)
=>5(2x+4)=197
=>2x+4=197/5
=>2x=177/5
hay x=177/10
d: \(\Leftrightarrow\left(19x+50\right):14=5^2-4^2=9\)
=>19x+50=126
=>19x=76
hay x=4
e: \(\Leftrightarrow2\cdot3^x=10\cdot3^{12}+8\cdot3^{12}=18\cdot3^{12}\)
\(\Leftrightarrow3^x=3^2\cdot3^{12}=3^{14}\)
hay x=14
f: \(\Leftrightarrow3\left(x+2\right):7=30\)
=>3(x+2)=210
=>x+2=70
hay x=68
g: \(2480-1570+200-x+5=1010\)
=>1115-x=1010
hay x=105
a)\(\frac{3^6}{3^2}+2^3\cdot2^2\)
\(\frac{3^6}{3^2}=3^4\)
\(2^3\cdot2^2=2^5\)
\(3^4+2^5=81+32=113\)
b)\(\left(13-12\right)^{2015}=1^{2015}=1\)
\(5.5^2=5^3=125\)
\(3.3^2=3^3=27\)
\(1+125+27=153\)
c)\(7.3^2-2.3^5+3^2=63-486+9=-414\)
\(5.2^2-18:3\)
\(=5.4-18:3\)
\(=20-6=14\)
\(2^3.17-2^3.14\)
\(=8.17-8.14\)
\(=8.\left(17-14\right)\)
\(=8.3\)
\(=24\)
\(75-\left(3.5^2-4.2^3\right)\)
\(=75-\left(3.25-4.8\right)\)
\(=75-\left(75-32\right)\)
\(=75-43\)
\(=32\)
\(150+50:5-2.3^2\)
\(=150+50:5-2.9\)
\(=150+10-18\)
\(=142\)
#Rảnh
\(32:\left(x+2\right)^3+2.5^2=2.3^3\)
\(32:\left(x+2\right)^3+50=54\)
\(32:\left(x+2\right)^3=4\)
\(\left(x+2\right)^3=8\)
\(\Rightarrow x+2=2\)
\(x=0\)